MINAT BELI BATIK PUCON DI JAKARTA - Noor, Laili Savitri; Nurapriyanti, Dita Nurapriyanti; Alkaf, Fatima Tuzzahara (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This article discussing the relationship between price, product innovation, lifestyle and buying interest Design/methodology/approach- Data were collected from 70 consumers from 3 (three) malls in Jakarta with data analysis techniques through multiple linear regression. Findings-The findings partially confirm that pricing and product innovation strategies do not support buying interest while lifestyles support buying interest. The findings simultaneously confirm that price strategy, product innovation, and lifestyle support buying interest. Implications-The results of this study are expected to be an input that can be considered for companies in determining pricing policies and providing innovation in products by adjusting current lifestyles so that consumer-buying interest will increase. As for consumers,it is hoped that this research will become additional information so that in the future it is more detailed and observant in buying a product that is innovative, quality, and not old-fashion. Keywords: Price, Product Innovation, Lifestyle, Purchase Interest